Characterization and structure determination of a llama‐derived nanobody targeting the J‐base binding protein 1. Issue 11 (2nd November 2018) - van Beusekom, Bart; Heidebrecht, Tatjana; Adamopoulos, Athanassios; Fish, Alexander; Pardon, Els; Steyaert, Jan; Joosten, Robbie P.; Perrakis, Anastassis
Abstract : A camelid single‐domain antibody fragment (nanobody) is shown to have high affinity towards its recognition target, the J‐base binding protein 1. The serendipitous crystallization of this nanobody alone, solution of its crystal structure and its refinement to 1.64 Å resolution are described. Ensemble refinement suggests that in the ligand‐free state one of the complementarity‐determining regions (CDRs) is flexible, while the other two adopt well defined conformations. Abstract : J‐base binding protein 1 (JBP1) contributes to the biosynthesis and maintenance of base J (β‐d ‐glucosylhydroxymethyluracil), a modification of thymidine confined to some protozoa. Camelid (llama) single‐domain antibody fragments (nanobodies) targeting JBP1 were produced for use as crystallization chaperones. Surface plasmon resonance screening identified Nb6 as a strong binder, recognizing JBP1 with a 1:1 stoichiometry and high affinity ( K d = 30 n M ). Crystallization trials of JBP1 in complex with Nb6 yielded crystals that diffracted to 1.47 Å resolution. However, the dimensions of the asymmetric unit and molecular replacement with a nanobody structure clearly showed that the crystals of the expected complex with JBP1 were of the nanobody alone. Nb6 crystallizes in space group P 31 with two molecules in the asymmetric unit; its crystal structure was refined to a final resolution of 1.64 Å. Ensemble refinement suggests that in the ligand‐free state one of the complementarity‐determining regions (CDRs) is flexible, while the other two adopt well defined conformations.